2020
DOI: 10.3168/jds.2020-18613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oscillating dietary crude protein concentrations on production, nutrient digestion, plasma metabolites, and body composition in lactating dairy cows

Abstract: We hypothesized that dairy cows fed oscillating metabolizable protein (MP) and crude protein (CP) concentrations on a 24-h frequency for a diet formulated to be below MP requirements would use N more efficiently (i.e., increased milk protein yields and less manure N) without increasing mobilization of body protein stores than would cows fed the same deficient MP diet continuously, although both treatments would on average have equal MP concentrations. In a randomized block design, 30 Holstein cows (119 ± 21 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
8
8
1
Order By: Relevance
“…Effects of dietary CP oscillation in ruminants remain ambiguous, and reported effects on NUE range from considerably negative (Ludden et al, 2002a) to substantially positive (Cole, 1999;Archibeque et al, 2007b;Doranalli et al, 2011). Recently, Tebbe and Weiss (2020) demonstrated that dairy cows receiving an oscillating CP diet (11.9% and 16.2% CP, 24-h basis) performed similarly in NUE, milk protein, and ECM yield to cows receiving a static CP diet (14.1% CP), in agreement with the present experiment. However, their reported lower N intake by cows with oscillating diet contrasts with our lack of treatment effect on N intake.…”
Section: Overall Effects Of Dietary Cp Oscillationssupporting
confidence: 89%
See 4 more Smart Citations
“…Effects of dietary CP oscillation in ruminants remain ambiguous, and reported effects on NUE range from considerably negative (Ludden et al, 2002a) to substantially positive (Cole, 1999;Archibeque et al, 2007b;Doranalli et al, 2011). Recently, Tebbe and Weiss (2020) demonstrated that dairy cows receiving an oscillating CP diet (11.9% and 16.2% CP, 24-h basis) performed similarly in NUE, milk protein, and ECM yield to cows receiving a static CP diet (14.1% CP), in agreement with the present experiment. However, their reported lower N intake by cows with oscillating diet contrasts with our lack of treatment effect on N intake.…”
Section: Overall Effects Of Dietary Cp Oscillationssupporting
confidence: 89%
“…Time frequency of the oscillation was different between these experiments, but amplitude and concentration of dietary protein, phase of lactation, and parity were comparable between studies. Reduced N intakes may therefore be related to a shorter frequency of oscillation used by Tebbe and Weiss (2020). In line with this, in our experiment, DMI of OS cows tended to be smaller than that of ST cows in the first 24 h, but not the subsequent 24 h, within a 48-h phase of feeding LP.…”
Section: Overall Effects Of Dietary Cp Oscillationssupporting
confidence: 85%
See 3 more Smart Citations